Analysis of the Radiator Loss Safety Boundary of a Space Reactor Gas Turbine Cycle with Multiple PCU Modules - Wenkui Ma; Ping Ye; Yue Gao; Yadong Hao; Yi Yao; Xiaoyong Yang (Energies, 2024)
The development of space exploration technologies puts higher demand on space power systems. The space reactor gas turbine cycle (SRGTC) has the advantages of compact configuration and small mass and volume and is one of the optimal options for future high-power space power systems. The SRGTC operates in an isolated island state and the radiator is fragile if it is hit by asteroids and space debris. The transient characteristics of the SRGTC are fundamental for safe operation in radiator loss accidents. In this paper, a dynamic model for the SRGTC is established, and the performance of the SRGTC with dual power conversion unit (PCU) modules (SRGTC-DPCU) after radiator loss was investigated. The results indicated that the waste heat of the system was accumulated in the radiator after radiator loss, which increased the consumed power of the compressor and further led to speed fluctuations. The bypass valve control and the temperature negative feedback effect can ensure the safe operation of the shaft and the reactor. More radiator loss decreased the speed far below the rated speed and exceeded the safety margin of the bypass valve control, which further led to system shutdown. There is a safety boundary of radiator loss accidents. Furthermore, the coupling effects of multiple PCUs after radiator loss were analyzed. The working fluid inventory was redistributed among the PCU modules. The reduction of working fluid inventory in the accident PCU module promoted the safety boundary. This study provides a reference for the operation of the SRGTC.